Do Populists Represent? Theoretical Considerations on How Populist Parties (Might) Enact their Representative Function. Issue 4 (2nd October 2019) - Werner, Annika; Giebler, Heiko
ABSTRACT: Are populist parties bad for representative democracy or are they filling a representative gap? While it has been broadly established that the emergence and success of populist parties is not merely a sign of protest, there is still a sparsity of empirical investigations into whether these parties represent hitherto under- or unrepresented social groups or whether they offer a policy profile that was in demand but not present. Using Pitkin's concepts of symbolic, descriptive and substantive representation, this article opens up the dimensions in which populist parties might challenge or aid democratic representation. It then places the articles in the Special Issue 'Populist Representation of, by and for the People?' along these dimensions and highlights their specific contributions.